Youth environmental activism - Banjac, Marinko (Teorija in praksa, 2024)
The article addresses different forms of youth environmental activism, starting from the phenomenon of the ambivalent position held by young people in environmental activism where on one hand they stand up for structural and radical change and, on the other, they cooperate with the authorities or at least make demands of them, thereby giving them legitimacy. The paper focuses on the relationship of young resisting subjectivities towards power and their interplay with strategies and practices and power mechanisms in the field of environmental regulation. The paper addresses various forms of youth environmental activism, especially looking at young dissenting subjectivities’ relationship to power and their intertwining with governing strategies and practices in the environmental field. Focus is given to the ways in which young activists are implicated in, constituted within, and respond to power relations and the exercise of governing, particularly when it comes to environmental issues. It draws on the Foucauldian approach of eco-governmentality and the analytical concept of counter-conduct as an analytical concept to examine how young activists address, co-constitute and potentially subvert or undermine power structures. Using this approach, we reflect on the diversity of agency found in youth activism, which includes an examination of the different forms, actions, strategies and practices associated with this activism.
Keywords: counter counduct; eco-governmentality; ekovladnost; environmental activism; mladi; Mladina; okoljski aktivizem; political ecology; politična ekologija; Politična participacija; protidelovanje; youth